What are the predictive factors of caecal perforation in patients with obstructing distal colon cancer?. (2nd August 2018) - Sabbagh, C.; Siembida, N.; Yzet, T.; Robert, B.; Chivot, C.; Browet, F.; Mauvais, F.; Regimbeau, J. M.
Abstract: Aim: In the presence of large bowel obstruction, the choice of treatment is determined by the patient's general status, the tumour characteristics and the perceived risk of caecal perforation. This study was designed to evaluate the predictive factors of impending caecal perforation, and also investigated the use of caecal volumetry. Method: From January 2011 to June 2016, patients with obstructive distal colon cancer undergoing emergency laparotomy, for whom a pretreatment CT scan was available, were included in this retrospective, case–control, two‐centre study. Two patient groups were defined: patients with and without impending caecal perforation. The primary end‐point of the study was a determination of predictive factors for caecal perforation. Results: A total of 72 patients (45 men, 62.5%) were included. Univariate analysis revealed that the presence of pericaecal fluid ( P < 0.0001), caecal pneumatosis ( P < 0.0001), mean maximum caecal diameter ( P = 0.001), mean caecal diameter at the ileocaecal junction ( P = 0.0001) and mean caecal volume ( P = 0.001) were associated with caecal perforation. Receiver operating characteristic curve analysis revealed that a caecal volume greater than 400 cm 3 ( P < 0.0001), a maximum caecal diameter > 9 cm ( P = 0.002) and a caecal diameter at the ileocaecal junction > 7.5 cm ( P = 0.001) were associated with impending caecal perforation. In multivariate analysis, only caecal volume > 400 cm 3 ( P = 0.001) was correlated with the risk of impending caecal perforation. Conclusion: Caecal volumetry is an easy and useful tool to predict impending caecal perforation in patients with large bowel obstruction.